Potrzebuję PILNIE!!!!!!! proszę ;(
rozwiaz równania i sprawdź poprawnośc rozwiązania
a) (x-1)² = x²
...- 2x +... = x² | -x²
-2x + ... = ... | - 1
-...= -1|: ...
x= ...
spr. ( ... - 1)² = x²
b) 3x + (6x + 1 ) = 4(5 + 9x²)- 4

c)(-3x+6)² - 2 = 3x(3x - 11) + 31

d) (-6x + 2 )² = -3(4-12x²)

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-20T21:42:53+01:00
A) (x-1)² = x²
x² - 2x + 1= x² |
x² - x² -2x = -1
-2x = -1|: (-2)
x= 1/2
spr. (1/2 - 1)² = 1/2²
1/4 - 2*1/2 + 1 = 1/4
1/4 - 1 + 1 = 1/4
1/4 = 1/4

b) 3x + (6x + 1)² = 4(5 + 9x²)- 4
3x + 36x² + 12x +1 = 20 + 36x² - 4
36x² - 36x² + 3x + 12x = 15
15x = 15
x = 1
Spr
3x + (6x + 1)² = 4(5 + 9x²)- 4
3 * 1 + (6 * 1 + 1 )² = 4 (5 + 9 *1²) - 4
3 + 7² = 4 * 14 - 4
3 + 49 = 56 - 4
52 = 52

c)(-3x+6)² - 2 = 3x(3x - 11) + 31
(6 - 3x)² - 2 = 3x(3x - 11) + 31
36 - 36x + 9x² - 2 = 9x² - 33x + 31
9x² - 9x² - 36x + 33x = 31 - 34
- 3x = - 3
x = 1
spr
(-3x+6)² - 2 = 3x(3x - 11) + 31
(- 3 * 1 + 6)² - 2 = 3*1 (3 * 1 - 11) + 31
3² - 2 = 3 * (-8) + 31
9 - 2 = -24 + 31
7 = 7
d) (-6x + 2 )² = -3(4-12x²)
36x² - 24x + 4 = - 12 + 36x²
36x² - 36x² -24x = - 16
-24x = -16 /:(-24)
x = 2/3
spr
(-6x + 2 )² = -3(4-12x²)
(-6* 2/3 + 2)² = -3 (4 - 12 *(2/3)²)
(- 4 + 2 )² = - 3 * (4 - 12 * 4/9)
(-2)² = -3 * (4 - 16/3)
4 = - 3 * (-4/3)
4 = 4

1 5 1